Anwendung von Matrizen für algebraische und andere Operationen mit Potenzreihen - Jasiulionis, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Ясюлионис. Применение матриц при алгебраических и некоторых других действиях со степенными рядамиA. Jasiulionis. Matricų taikymas laipsninių eilučių algebriniams ir kai kuriems kitiems veiksmams atlikti